Pengaruh Brand Awareness, Kualitas Proyek Dan Kepercayaan Terhadap Keputusan Berdonasi Secara Online Pada Platform Crowdfunding Kitabisa.Com. - Annisyah Paradhita Sari; M Ridwan; S Sugianto (TANSIQ: Jurnal Manajemen Dan Bisnis Islam, 2019)
This study aims to determine how much the influence of brand awareness, project quality, and trust in decisions to donate at Kitabisa.com. The research approach used is a quantitative research approach. The sample in this study were users who donated at Kitabisa.com with a total sample of 145 people. The instrument used to obtain data is a questionnaire using a Likert scale. This study uses multiple linear regression analysis. supported by Validity and Reliability test, Classical Assumption Test, t-test and f-count test using SPSS version 22 software. The results of this study indicate that simultaneously, variable of brand awareness, project quality, and trust have a significant effect on donation decisions at Kitabisa.com and the results of the test partially show that all independent variables, namely brand awareness, project quality, and trust, each have a significant effect on the decision to donate at Kitabisa.com.